1974
DOI: 10.1073/pnas.71.5.1715
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Five Antibiotic Resistances at the Subunit Level in Chloroplast Ribosomes of Chlamydomonas

Abstract: The chloroplast ribosomes from five antibiotic resistant strains of Chlamydomonas, each carrying one mutant gene mapping in chloroplast DNA, have been shown to be resistant to the corresponding antibiotic in a poly(U)-directed amino-acid incorporating assay system. The alteration conferring resistance was localized to the 30S subunit in ribosomes from streptomycin, neamine, and spectinomycin resistant strains, and to the 50S subunit in ribosomes from cleocin and carbomycin resistant strains. Spectinomycin resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1974
1974
1987
1987

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…An association between 16S rRNA and the streptomycin-resistance phenotype examined here is consistent with the fact that nonmendelian mutations for streptomycin resistance in C. reinhardtii affect the small ribosomal subunit of the chloroplast (17,18). Nevertheless, our data do not exclude the possibility that the streptomycinresistance phenotype is associated with an altered ribosomal protein such as the ribosomal protein S12 of Escherichia coli (19) and that the locus for this protein is closely linked to one of the 16S rRNA genes.…”
Section: Discussionsupporting
confidence: 51%
“…An association between 16S rRNA and the streptomycin-resistance phenotype examined here is consistent with the fact that nonmendelian mutations for streptomycin resistance in C. reinhardtii affect the small ribosomal subunit of the chloroplast (17,18). Nevertheless, our data do not exclude the possibility that the streptomycinresistance phenotype is associated with an altered ribosomal protein such as the ribosomal protein S12 of Escherichia coli (19) and that the locus for this protein is closely linked to one of the 16S rRNA genes.…”
Section: Discussionsupporting
confidence: 51%
“…Primarily due to a number of advantageous biological characteristics, Chlamydomonas reinhardtia, a unicellular green alga, has been increasingly exploited for fruitful investigations of the cooperation between chloroplast and nuclear genomes in nucleic acid metabolism (1)(2)(3)(4) and protein synthesis (5,6). Genetic studies with a few non-Mendelian mutants have also suggested that there is probably another level of cooperation between the chloroplast and mitochondria genomes in organelle protein synthesis (7)(8)(9).…”
mentioning
confidence: 99%
“…Wild type Chlamydomonas reinhardi strain 21gr, used in these experiments, was grown on minimal medium (12) in continuous light (15,(0)(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17),000 lux) at 250. Cultures larger than 100 ml were bubbled with 55% CO2 in air.…”
Section: Methodsmentioning
confidence: 99%
“…The specificity of action of the protein synthesis inhibitors used (spectinomycin, streptomycin, neamine, chloramphenicol, and cleocin), has recently been established in Chlamydomonas by studies of amino acid Abbreviations: EDTA, ethylene diaminetetraacetate; TCA, trichloroacetic acid; n/t, cpm in nuclear fraction divided by cpm in nuclear + chloroplast fractions X 100. * incorporating activity of purified chloroplast and cell sap ribosomes taken from wild-type and from drug-resistant mutant strains, in a poly(U) directed assay system (9). The specificity of action of rifampicin in Chlamydomonas (10) and of rifamycin SV in various systems (11) has been investigated by others.…”
mentioning
confidence: 99%